1965
DOI: 10.1071/bi9650917
|View full text |Cite
|
Sign up to set email alerts
|

The Absorption of Lactic Acid from the Reticulo-Rumen of the Sheep

Abstract: SummaryA series of acute experiments has been carried out on sheep to study some of the factors which influence the rate of absorption of lactic acid from the ligated washed·out forestomachs.The rate of absorption of lactic acid was faster from an 0 ·12M than from an O· 06M solution and faster from a solution at pH 4 than from a solution at pH 5. The absorption rate was less from a solution with a tonicity of 440 m·osmoles than from a solution with a tonicity of 300 m-osmoles. The absorption rate of lactic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
2

Year Published

1973
1973
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 10 publications
6
15
2
Order By: Relevance
“…Umesaki et al [27] concluded that the rates of absorption of lactic and succinic acids in the rat colon were about one hundredth of the SCFAs absorption. In other reports, it was noted that the mean absorption rates of lactic acid were about 8% [32] and 10% [1] of that of SCFAs.…”
Section: Discussionmentioning
confidence: 99%
“…Umesaki et al [27] concluded that the rates of absorption of lactic and succinic acids in the rat colon were about one hundredth of the SCFAs absorption. In other reports, it was noted that the mean absorption rates of lactic acid were about 8% [32] and 10% [1] of that of SCFAs.…”
Section: Discussionmentioning
confidence: 99%
“…Lactic acid is a much stronger acid (pK 3 8) than the VFAs (pK 4-7-48) and the pH must be correspondingly lower, or the total acid concentration much higher in order to achieve a similar concentration of undissociated acid, for it is the latter value, rather than the total acid concentration that is important for the absorption (Williams & Mackenzie, 1965), excitation of acid-sensitive receptors (Leek & Harding, 1975) and inhibition of motility (Upton et al 1976). Due to the corrosive effect of lactic acid (Dunlop & Hammond, 1965;Ahrens, 1967) infusions of lactic acid were performed only once in any animal, as the last experiment, and in only two cases was infusion continued until abolition of motility occurred.…”
Section: Discussionmentioning
confidence: 99%
“…For the ten trials absorp tion rates of total VFA expressed as mmol/h per kg body weight averaged 3.11 with a range of 1.34-4.84. These results and especially those of trials 6 and 8 obtained with test solutions containing 75mmol/l total VFA at pH 6.0 are similar to the rates reported by Williams & Mackenzie (1965 Leng & Brett (1966) and Leng & Leonard (1965) determined ruminai VFA production rates in fed sheep by isotope dilution techniques. Production rates in mmol/h per kg body weight calculated from their results are comparable to the absorption rates observed in the present study, but generally tend to be somewhat higher, especially the production rates for acetate.…”
Section: Discussionsupporting
confidence: 76%
“…Relative absorption rates calculated from his data also indicated that the marked differences in the individual rates at which acetic, propionic and butyric acids were absorbed at pH 4 tended to de crease as the pH of the VFA solutions was raised to 7.8. This trend confirms the observation by Williams & Mackenzie (1965).…”
Section: Review Of Literaturesupporting
confidence: 82%
See 1 more Smart Citation